péritonites aigues généralisées : etude retrospective de cas operes a L'EPH de laghouat - HOCINE Iman Fatiha; REZIGUI Asmaa; Dr. BENMOUFFOK Ali (Université Amar Telidji de Laghouat Faculté de Médecine, 2021)
Generalized acute peritonitis is a medico surgical emergency that is defined as a brutal and diffuse peritoneum inflammatory. We performed a retrospective descriptive study whose objective was to describe the diagnostic and therapeutic aspects of acute generalized peritonitis operated in PHE of Laghouat. The data covering the period from 2019 to 2020 was collected from hospital records, operative reports and medical records of surgical service. We recorded 69 cases of acute generalized peritonitis treated for abdominal emergencies 446 mean 15.46%. The sample consisted of 79.71% of male subjects. The average age of patients was 37.50 years (extremes: 16 and 80 years). Aetiology of acute generalized peritonitis found were complicated appendicitis (42.03%), Gastro duodenal perforations (42.03%), small intestinal and Colonic perforations (7.25%), Postoperative peritonitis (5.79%), 01 case of subinfected peritoneal tuberculosis, and 01 case of perforated mesenteric infarction. We found that Morbidity was 7.25%. Mortality was 5.8%. Generalized peritonitis remains a serious condition. The improved prognosis through a diagnosis and early treatment of causal injury and require the intervention of a multidisciplinary team.
96.p